The Global Financial Crisis : Comparisons with the Great Depression and Scenarios for Recovery - Brahmbhatt, Milan (World Bank, Washington, DC, 2012)
A recent paper has highlighted some close correspondences between economic performance during the present world recession and that during the early months of the great depression that began in late 1929. World industrial production from April 2008 to April 2009 fell as rapidly as during the first year of the great depression, while stock market prices and world trade volumes have fallen more rapidly than in the comparable period. These comparisons lead Eichengreen and O'Rourke to draw the alarming conclusion that 'it's a depression alright.' They note, however, that fiscal and monetary policies are likely to be much more supportive of economic activity in the next 1-2 years than they were during the first few years of the great depression. The first part of this note outlines some other important structural differences between the world economy today and in the 1930s that are likely to affect how the present recession plays out relative to the great depression. The second part of the note discusses possible recovery paths out of the current crisis.